ANALISIS PESERTA DIDIK YANG TERISOLIR DI MAN 2 PONTIANAK TAHUN 2019 - Amalia, Sri Rezeki; Yuline, Yuline; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIsolated is a child who does not have friends in the association because he or she does not have the interest to participate in group activities as a social process. This happens because of the lack of social attitudes of isolated students. Every student in MAN 2 Pontianak is expected to have a social attitude but there are still isolated students. In general, this study aims to obtain a picture of â€œIsolated Students in Man 2 Pontianak in 2019â€. (1) Internal factors that affect students who are isolated in MAN 2 Pontianak. (2) External factors that affect students who are isolated in MAN 2 Pontianak. (3) Impacts that occur from students who are isolated in MAN 2 Pntianak. (4) Assistance that has been done by guidance and conseling teacher for students who are isolated in MAN 2 Pontianak. The method used is descriptive method and the form of research is survey research. The subjects in this study were five students and their close friends and one guidance and counseling teacher. This study used a qualitative approach and data collection techniques used were observation, interview, documentation and sociometry. Based on the results of the study, the internal factors of isolated students are (1) Students cannot adjust themselves, (2) Reserved, (3) Introverted. External factors, namely (1) Rejection from groups, (2) Neglected from groups. The impacts of isolation are (1) Always alone, (2) Studentsâ€™ value decreased, (3) Cannot socialize properly. Assistance provided by guidance and counseling teacher in dealing with isolated cases are (1) Providing Classical Services, (2) Providing Invidual Counseling, (3) providing group guidance (4) Providing Group Counseling.Keywords: External Factors, Internal Factors, Isolated Impacts, Students